Transient cardiac responses to witnessing horrible events in young adult female exercisers and non-exercisers. (January 2016) - Lackner, Helmut K.; Weiss, Elisabeth M.; Hofer, Ellen; Rössler, Andreas; Fink, Andreas; Schulter, Günter; Papousek, Ilona
Abstract: Objectives: It has been proposed that regular exercisers may be less vulnerable to the effects of stress and better able to cope with aversive events than people who are sedentary, but findings have not been consistent. In the present study, physiological variables indicating specific relevant psychological processes were used to objectively assess women's responses to stressful events. Design and Method: Non-exercising ( n = 56) and regularly exercising women (up to 4 h, n = 62, and more than 4 h per week, n = 50) were viewing an aversive film consisting of scenes of real injury and death, and their transient cardiac responses to sudden horrifying events happening to persons in the film were obtained, as well as changes of prefrontal-posterior coupling, measured by EEG. Results: Compared to regularly exercising women, non-exercising women showed a clearly more pronounced second accelerative component of the transient heart rate response to the terrifying events, indicating greater sensitivity of the avoidance (defensive) motivational system and heightened sensitivity to aversive stimuli. Moreover, non-exercising women did not show the expected characteristic initial heart rate acceleration when the scene approached its fatal end, that is, more rigid responding, and EEG data indicated less susceptibility to affect-laden information at the perceptual level. Conclusions: The findings support the notion of less adaptive coping with adverse events in sedentary compared to exercising women and add to the growing evidence suggesting a stress-buffering effect of regular exercise, therefore promoting resilience and resistance to the negative impact of stressor and trauma exposure. Highlights: Innovative approach of the combined use of cardiac (ECG) and brain (EEG) data. Impact of aversive film consisting of scenes of real injury and dead was studied. Regular exercisers were better able to cope with aversive events. Results support the evidence of a stress-buffering effect of regular exercise.